Identifikasi Lapisan Pembawa Mineral Emas dengan Metode Resistivitas dan Induksi Polarisasi di Desa Paningkaban Kecamatan Gumelar Kabupaten Banyumas Jawa Tengah - Nandi Maulani Nasruddin; Aditya Verry Saputra; Mia Durrotun Nafisah; Sehah Sehah (Lambung Mangkurat University Press, 2020)
The research has been done in the Paningkaban village, Gumelar District, Banyumas Regency, Central Java Province. This research aims to identify technically the presence of gold mineral distribution using the method of geoelectricity-resistivity and induced polarization (IP), to interpret the obtained resistivity and chargeability data from the research area, to determine the subsurface structure model in the reasearch area, and find out the potential of gold in the research area i.e Paningkaban. The method in this research includes field data acquisition, data processing, and data interpretation. The acquisition uses a syscal resistivitymeter tools by stretching 200 meters of cable on each track that has been connected to the electrode and porous pot. The results obtained from the acquisition are primary data which are still in the form of voltages, currents, and apparent chargeability values. Based on this data, the processing is carried out to obtain the resistivity and chargeability profiles so that can be interpreted and correlated. The correlation between the resistivity and chargeability data was carried out to identify the gold mineralization zone in two dimensions. The presence of gold mineralization is characterized by the emergence of rocks with a low resistivity value and high chargeability because mineralization in the geological area is seen in quartz veins. Quartz veins are common features of many deposits and are indicative of the presence of mineralization, especially gold. Based on the results of the interpretation, the subsurface rock which contain gold minerals are found on each line, with resistivity values ranging from 4,25 – 17,3 Ωm and the chargeability value ranges from 26,4 – 226 msec. These rocks which are estimated to contain gold minerals are the sandy clay.